The fort - Korman, Gordon (New York : Scholastic Press, 2022)
Five middle schoolers find a fully stocked bomb shelter constructed decades ago in the local woods by an eccentric tycoon and lost until a hurricane exposes the entrance. So, how to keep the hideout secret from interfering grown-ups--and, more particularly, from scary teen psychopath Jaeger Devlin.
Keywords: Nuclear bomb shelters -- Juvenile fiction; Friendship -- Juvenile fiction; Secrecy -- Juvenile fiction; Family violence -- Juvenile fiction; Middle school boys -- Juvenile fiction; Nuclear bomb shelters -- Fiction; Friendship -- Fiction; Secrets -- Fiction; Family violence -- Fiction; Middle school boys -- Fiction; Domestic fiction